2017
DOI: 10.1039/c6cs00693k
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the detection and identification of pathogenic bacteria: past, present, and future

Abstract: In order to retard the rate of development of antibacterial resistance, the causative agent must be identified as rapidly as possible, so that directed patient treatment and/or contact precautions can be initiated. This review highlights the challenges associated with the detection and identification of pathogenic bacteria, by providing an introduction to the techniques currently used, as well as newer techniques that are in development. Focusing on the chemical basis for these techniques, the review also prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
263
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(264 citation statements)
references
References 44 publications
0
263
0
1
Order By: Relevance
“…To explain, the conventional susceptibility methods require at least 24 h following an overnight inoculation (16-20 h) and in the case of agar-based methods (disk diffusion, E test), poor diffusion of vancomycin has been observed and caused false negative (indicating susceptibility rather than resistance) results. In one study, Váradi et al [25] found that phenotypic methods for the identification of pathogenic bacteria are associated with limitations such as error in detection, low sensitivity and specificity, and low speed in identifying large numbers of samples. Moreover, the major challenge for all methods is detecting heteroresistant species.…”
Section: Dehbashi Et Al Tropical Medicine and Healthmentioning
confidence: 99%
“…To explain, the conventional susceptibility methods require at least 24 h following an overnight inoculation (16-20 h) and in the case of agar-based methods (disk diffusion, E test), poor diffusion of vancomycin has been observed and caused false negative (indicating susceptibility rather than resistance) results. In one study, Váradi et al [25] found that phenotypic methods for the identification of pathogenic bacteria are associated with limitations such as error in detection, low sensitivity and specificity, and low speed in identifying large numbers of samples. Moreover, the major challenge for all methods is detecting heteroresistant species.…”
Section: Dehbashi Et Al Tropical Medicine and Healthmentioning
confidence: 99%
“…Several tests are then performed to address genus identification, namely microscopy cell staining, colony morphology, and rapid biochemical tests. To perform identification at the species level, the more common methods are phenotypically based, such as manual (e.g., Api bioMérieux) and automated biochemical tests, which exploit the differences in protein expression within genus (or also between genera), providing a characteristic protein expression fingerprint with a relatively high degree of certainty . For example, the OmniLog ID system (Biolog) is a rapid method for the phenotypic identification of bacteria and fungi, through their ability to oxidize different carbon sources.…”
Section: Current Technologies For Bacterial Identification and Antibimentioning
confidence: 99%
“…Also, some special enzymes like β‐lactamases are produced owing to the bacterial gene mutations, and these enzymes can specifically target certain chemical structures in their substrates to damage the structures . Notably, these enzymes might be produced specifically by a certain bacterial strain, thus providing the theoretical basis for specific detection or targeting of bacteria …”
Section: Physiological Factors At Infection Sites and Their Functionsmentioning
confidence: 99%
“…Theoretically, each bacterial strain possesses its own unique character, distinguishing itself from other bacterial strains. However, mainly limited by the detection methods or equipment, the most commonly used methods to detect bacteria are chromogenic or fluorogenic methods, especially the small molecule probes. The adaptive, fluorescent, or chemiluminescent small molecule bacterial probes typically contain three subunits, including a bacterial‐enzyme‐targeting moiety, an enzyme‐cleavable chemical bond, and a chromogen or fluorogen ( Scheme 1 ).…”
Section: Infection Detectionmentioning
confidence: 99%